A critical review of Chinese and international social work: Walking a tightrope between local and global standards. (November 2022) - Meng, Qian; Gray, Mel; Bradt, Lieve; Roets, Griet
This article presents a critical analysis of the challenges global social work standards present for mainland China (hereafter China) with its authoritarian political ideology that is in tension with the profession's universal values grounded in liberal individualism. China is caught between the Scylla of universal standards and Charybdis of indigenisation seeking to adapt social work to its unique sociocultural contexts. Based on our extensive literature review, we identified four challenges for Chinese social work: (1) balancing personal social services and social development, (2) negotiating global standards and local realities, (3) responding to poverty and other national social development issues and (4) pressures towards indigenisation, while remaining in step with social work's global standards. China favours the continued adaptation of imported knowledge and practice interventions within local and national sociocultural, economic and political realities. This study also highlights social work in China's urban bias and limited attention to rural issues, acknowledging this is a concern for social work even in Western contexts.